2022
DOI: 10.3389/fmolb.2021.762541
|View full text |Cite
|
Sign up to set email alerts
|

BTBD10 is a Prognostic Biomarker Correlated With Immune Infiltration in Hepatocellular Carcinoma

Abstract: Background: BTBD10 serves as an activator of Akt family members through decreasing the protein phosphatase 2A-mediated dephosphorylation. The present study attempted to investigate the prognostic value of BTBD10 in hepatocellular carcinoma (HCC), specially, its relationship with tumor-infiltrating lymphocytes (TILs).Methods: BTBD10 expression was evaluated in HCC using The Cancer Genome Atlas (TCGA) and Xijing Hospital database, and verified in HCC cell lines. Cox analyses were performed to analyze independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…BTBD10 was known to activate AKT by inhibiting PP2A-mediated dephosphorylation and inactivation of AKT [ 52 ]. Studies have reported that BTBD10 is a prognostic biomarker in cancer and associated with immune infiltration such as glioma [ 53 ], and hepatocellular carcinoma [ 54 , 55 ]. Furthermore, a decrease in BTBD10 expression has been linked to motor neuron death in cases of amyotrophic lateral sclerosis cases due to the downregulation of the AKT-mediated prosurvival signal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…BTBD10 was known to activate AKT by inhibiting PP2A-mediated dephosphorylation and inactivation of AKT [ 52 ]. Studies have reported that BTBD10 is a prognostic biomarker in cancer and associated with immune infiltration such as glioma [ 53 ], and hepatocellular carcinoma [ 54 , 55 ]. Furthermore, a decrease in BTBD10 expression has been linked to motor neuron death in cases of amyotrophic lateral sclerosis cases due to the downregulation of the AKT-mediated prosurvival signal [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified as an EMT and metastasis regulator in NPC ( 34 ) and NSCLC ( 35 ). BTBD10 functions as an activator of AKT family members by inhibiting PPP2CA-mediated dephosphorylation, and a few studies have identified it as a prognostic risk factor in hepatocellular carcinoma ( 36 ) and glioma ( 37 ). DLX1 serves as a two-sided transcriptional regulator of the TGF-β superfamily that may be either an oncogene or a suppressor in different types of tumors ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis has demonstrated that BTBD10 interacts with protein phosphatase 2A (PP2A) and inhibits the dephosphorylation of AKTs by PP2A, which indicates that BTBD10 can interact with PP2A to maintain AKT phosphorylation [ 36 ]. These results show that BTBD10 is an important AKT activator, which is an inhibitor of cell death by activating AKT [ 36 , 37 ]. Meanwhile, the results of transcriptome sequencing also showed that almost all the pathways enriched by DEGs were PIK3CB / AKT1- related, this further supports the hypothesis that PI3K/AKT signal is the key pathway for miR-202-5p to regulate the proliferation and apoptosis of goose GCs.…”
Section: Discussionmentioning
confidence: 99%